Impact of Seed Transmission of Bipolaris sorokiniana on the Planting Value of Wheat Seeds (Journal of Environmental Science and Natural Resources, 2012)
An experiment was conducted in vitro to determine the planting value of wheat seeds as affected by Bipolaris sorokiniana. The wheat seed samples were tested in blotter method and impairment caused by B. sorokiniana was recorded after sprouting of the seeds. During the germination of wheat seeds the pathogen transmitted from seed to plant and caused germination failure, coleoptile infection and root infection. Significantly, the highest transmission of the pathogen caused germination failure in the sample S2 (64.3%). The coleoptile infection was recorded in the sample S3 (9.5%) followed by S2 (5.4%) and S1 (2.4%) respectively. The pathogen was recorded to be transmitted from seed to the coleorhizae giving rise to significantly the highest infection in S3 (2.6%) followed by S2 (2.3%) and S1(2.1%) respectively in blotter. Regression between prevalence of the pathogen and germination failure along with the coleoptiles and coleorhizae infection indicated the increasing trend of deteriorating planting value of the seed with the increasing rate of transmission of the pathogen from seed to germinating seed and seedlings. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11556 J. Environ. Sci. & Natural Resources, 5(1): 75- 78, 2012